STRATEGI PENINGKATAN KOMPETENSI LITERASI INFORMASI MAHASISWA DALAM MENDUKUNG TRI DHARMA PERGURUAN TINGGI - Endang Fatmawati (Central Library of Universitas Sebelas Maret, 2019)
This article is to discuss the strategies to improve the competency of informationliteracy for college students and explain the benefits. Strategies are needed so thatthe college students has the competency of information literacy based on informationtechnology, namely: constantly upgrading the skills to follow user education, activetraining information literacy, must have the digital literacy skills, good at searchingthrough e-resources, mastering the techniques of information retrieval using a searchengine, active join to reference management tools training, as well as understand theethical use of information. Various benefits college students who always improvinginformation literacy competencies can help the academic community in terms makeit easier to find information strategy, facilitate access to electronic information, tomanage resources owned reference, and facilitate the writing of scientific papers.Keywords: competence; college students; information literacy; academic community